Rare Isotope Production in peripheral heavy-ion collisions at beam energy of 15 MeV/nucleon - Fasoula, O.; Souliotis, G. A.; Tshoo, K.; Jeong, S. C.; Kang, B. H.; Kwon, Y. K.; Veselsky, M.; Bonasera, A. (HNPS Advances in Nuclear Physics, 2019)
This paper presents our recent study on the production of neutron-rich rare isotopes with heavy-ion beams in the energy region of 15 MeV/nucleon. We present calculated production cross sections of neutron-rich nuclides from collisions of a 86Kr (15 MeV/nucleon) beam with 238U targets. Our calculations are based on a two-step approach: the dynamical stage of the collision is described with either the phenomenological Deep-Inelastic Transfer model (DIT), or with the microscopic Constrained Molecular Dynamics model (CoMD). The de-excitation of the hot heavy projectile fragments is performed with the Statistical Multifragmentation Model (SMM). We also performed calculations with a radioactive beam of 92Kr (15 MeV/nucleon) with a target of 238U and observed that the multinucleon transfer mechanism leads to very neutron-rich nuclides toward and beyond the astrophysical r-process path. In the future, we plan to experimentally investigate such reactions in the KOBRA spectrometer at the RISP facility in Korea. We conclude that the reaction mechanism at beam energies below the Fermi energy involving periph- eral nucleon exchange, constitutes a novel and effective route to access extremely neutron-rich isotopes toward the r-process path and the neutron drip-line.